To Anion–π or not to Anion–π: The Case of Anion‐Binding to Divalent Fluorinated Pyridines in the Gas Phase. Issue 49 (26th July 2018) - Göth, Melanie; Witte, Felix; Quennet, Marcel; Jungk, Phillip; Podolan, Gabriel; Lentz, Dieter; Hoffmann, Waldemar; Pagel, Kevin; Reissig, Hans‐Ulrich; Paulus, Beate; Schalley, Christoph A.
Abstract: A series of mono‐ and divalent fluorinated pyridine derivatives is investigated by electrospray ionization (tandem) mass spectrometry and quantum chemical calculations with respect to their capability to bind anions in the gas phase. The pyridine derivatives differ not only in valency, but also with regard to the degree of fluorination of the pyridine rings, the positions of the fluorine atoms, the rigidity of the spacers connecting the two pyridines in the divalent compounds, and the relative configuration. While the monovalent compounds did not form anion complexes, the divalent analogues exhibit anion binding even to weakly coordinating anions such as tetrafluoroborate. Three different tandem mass spectrometric experiments were applied to rank the gas‐phase binding energies: (i) collision‐induced dissociation (CID) experiments in a Fourier transform ion‐cyclotron‐resonance (FTICR) mass spectrometer on two different, simultaneously mass‐selected complexes with different receptors, (ii) determination of the collision energy required to fragment 50 % of the mass‐selected complexes in an ESI‐QToF mass spectrometer, and (iii) CID of heterodimers formed from two different, competing pyridine receptors and indigo carmine, a dianion with two identical binding sites. All three experiments result in consistent binding energy ranking. This ranking reveals surprising features, which are not in agreement with binding through anion–π interactions. Density functional theory (DFT) calculations comparing different potential binding modes provide evidence that the ranking can instead nicely be explained, when C−H⋅⋅⋅anion interactions with the spacers are invoked. These results are supported by gas‐phase IR spectroscopy and ion mobility‐mass spectrometry (IM‐MS) on a selected set of chloride pyridine complexes. Abstract : Do electron‐deficient fluorinated pyridines bind anions through anion–π interactions in the gas phase? Tandem mass spectrometric experiments with anion complexes of divalent fluorinated pyridines reveal trends of binding strengths that clearly rule out anion–π interactions to be important for complex formation. Density functional calculations instead suggest binding through C−H⋅⋅⋅anion contacts with polarized C−H bonds of the spacers between the two pyridines.